RECOVERY OF MAINTENANCE OBLIGATIONS IN POLISH-AMERICAN RELATIONS – END OF RECIPROCAL PRINCIPLE - Juryk, Anna (Review of European and Comparative Law, 2017)
This article concerns changes in recovery the child support and other forms of family maintenance in Polish-American relations after entered into force Convention of 23 November 2007 on the International Recovery of Child Support and Other Forms of Family Maintenance for the United States (1st January 2017) . These changes primarily concern: cooperation between Polish and American Central Authorities, recognition and enforcement of foreign judgments, applications and required documents and legal assistance as well as costs . The 2007 Convention is a hope for maintenance creditors for more effective and faster enforcement of maintenance in the United States and the similarity to the provisions of the Regulation (EU) No 4/2009 gives a chance for unified global cooperation between States in recovery of maintenance, as well as constitutes facilitation for central authorities examining applications EU and non-EU States based on similar principles .